Dynamics and Regulations of BimEL Ser65 and Thr112 Phosphorylation in Porcine Granulosa Cells during Follicular Atresia - Feng Yang (Cells, 2020)
BimEL protein is involved in follicular atresia by regulating granulosa cell apoptosis, but the dynamic changes of BimEL phosphorylation during follicular atresia are poorly understood. The aim of this study was to explore the changes of key BimEL phosphorylation sites and their upstream regulatory pathways. First, the levels of BimEL-Ser65 and BimEL-Thr112 phosphorylation (p-BimEL-S65, p-BimEL-T112) in granulosa cells (GC) from healthy (H), slightly-atretic (SA), and atretic (A) follicles and in cultured GC after different treatments were detected by Western blotting. Next, the effects of the corresponding site mutations of BIM on apoptosis of GC were investigated. Finally, the pathways of two phosphorylation sites were investigated by kinase inhibitors. The results revealed that p-BimEL-S65 levels were higher in GC from H than SA and A, whereas p-BimEL-T112 was reversed. The prosurvival factors like FSH and IGF-1 upregulated the level of p-BimEL-S65, while the proapoptotic factor, heat stress, increased the level of p-BimEL-T112 in cultured GC. Compared with the overexpression of wild BimEL, the apoptotic rate of the GC overexpressed BimEL-S65A (replace Ser65 with Ala) mutant was significantly higher, but the apoptotic rate of the cells overexpressing BimEL-T112A did not differ. In addition, inhibition of the ERK1/2 or JNK pathway by specific inhibitors reduced the levels of p-BimEL-S65 and p-BimEL-T112. In conclusion, the levels of p-BimEL-S65 and p-BimEL-T112 were reversed during follicular atresia. Prosurvival factors promote p-BimEL-S65 levels via ERK1/2 to inhibit GC apoptosis, whereas proapoptotic factor upregulates the level of p-BimEL-T112 via JNK to induce GC apoptosis.